Peran Anemia Sebagai Faktor Risiko Hipertensi Resisten pada Penyakit Ginjal Kronik - Nasution, Salwa Salsabila; Kurniati, Intanri; Ratna, Maya Ganda; Ramadhian, M. Ricky (Medula, 2025)
Anemia is one of the most common complications in chronic kidney disease (CKD) that significantly affects quality of life and prognosis. Anemia is a condition where there is a decrease in iron-rich hemoglobin levels, which functions to circulate oxygen throughout the body. Chronic kidney disease is a kidney condition characterized by abnormalities in kidney structure or function. Men have a 2 times higher risk of developing CKD than women due to their generally poorer lifestyle habits. The condition of insufficient oxygen perfusion to tissues leads to activation of the renin-angiotensin-aldosterone system (RAAS). The RAAS system ultimately produces aldosterone and antidiuretic hormones that cause sodium retention in the body and lead to increased blood pressure. Additionally, anemia can cause changes in blood vessels, where there is an increase in vascular resistance, especially in CKD patients. Studies have also shown that erythropoietin therapy can increase the prevalence of hypertension. Resistant hypertension is a condition where someone suffering from hypertension fails to achieve target blood pressure of <140/80 mmHg in normal individuals and <130/80 mmHg in CKD patients despite adhering to a combination dose of three types of antihypertensive medications. Someone suffering from resistant hypertension must comply with the drug dosage prescribed by the doctor and also improve their lifestyle. This article aims to understand how anemia serves as a risk factor for resistant hypertension in CKD patients. Furthermore, the diagnosis and treatment of resistant hypertension are also discussed in this article.